Incidence of deep vein thrombosis among non‐ICU patients hospitalized for COVID‐19 despite pharmacological thromboprophylaxis. (27th August 2020) - Santoliquido, Angelo; Porfidia, Angelo; Nesci, Antonio; De Matteis, Giuseppe; Marrone, Giuseppe; Porceddu, Enrica; Cammà, Giulia; Giarretta, Igor; Fantoni, Massimo; Landi, Francesco; Gasbarrini, Antonio; Pola, Roberto; et al.
Abstract: Background: A remarkably high incidence of venous thromboembolism (VTE) has been reported among critically ill patients with COVID‐19 assisted in the intensive care unit (ICU). However, VTE burden among non‐ICU patients hospitalized for COVID‐19 that receive guideline‐recommended thromboprophylaxis is unknown. Objectives: To determine the incidence of VTE among non‐ICU patients hospitalized for COVID‐19 that receive pharmacological thromboprophylaxis. Methods: We performed a systematic screening for the diagnosis of deep vein thrombosis (DVT) by lower limb vein compression ultrasonography (CUS) in consecutive non‐ICU patients hospitalized for COVID‐19, independent of the presence of signs or symptoms of DVT. All patients were receiving pharmacological thromboprophylaxis with either enoxaparin or fondaparinux. Results: The population that we screened consisted of 84 consecutive patients, with a mean age of 67.6 ± 13.5 years and a mean Padua Prediction Score of 5.1 ± 1.6. Seventy‐two patients (85.7%) had respiratory insufficiency, required oxygen supplementation, and had reduced mobility or were bedridden. In this cohort, we found 10 cases of DVT, with an incidence of 11.9% (95% confidence interval [CI] 4.98‐18.82). Of these, 2 were proximal DVT (incidence rate 2.4%, 95% CI −0.87‐5.67) and 8 were distal DVT (incidence rate 9.5%, 95% CI 3.23‐5.77). Significant differences between subjects with and without DVT were D‐dimer > 3000 µg/L ( P  < .05), current or previous cancer ( P  < .05), and need of high flow nasal oxygen therapy and/or non‐invasive ventilation ( P  < .01). Conclusions: DVT may occur among non‐ICU patients hospitalized for COVID‐19, despite guideline‐recommended thromboprophylaxis.